NAVIGATING COVID-19 IN PREGNANCY: CARE PATHWAYS AND SYSTEM CHALLENGES IN KAZAKHSTAN – A QUALITATIVE STUDY - Nurgaliyeva, Zhansaya; Glushkova, Nataliya (Srpski medicinski časopis Lekarske komore, 2026)
Introduction: International studies conducted during the COVID-19 pandemic have shown that pregnant women often experienced significant barriers to timely and appropriate care. However, much of the existing evidence is derived from quantitative surveillance or from settings with well-established digital infrastructure and standardized clinical pathways, which may not reflect the realities of many middle-income health systems. This study aims to qualitatively explore the experiences of pregnant women and healthcare professionals regarding COVID-19 care pathways, including symptom recognition, outpatient management, and hospitalization, in Almaty, Kazakhstan.  Methods: The present study applied a qualitative, descriptive, phenomenological design to explore how pregnant COVID-19 patients and healthcare professionals experienced the organization of care during the pandemic. The study included 24 participants from local primary health care and hospital settings in Almaty, Kazakhstan. Fifteen healthcare professionals and nine pregnant or postpartum women voluntarily and anonymously provided informed consent to in-depth semi-structured interviews, either face-to-face or via secure video conferencing, between May and August 2023. Results: Healthcare professionals reported that COVID-19 substantially altered maternal health care due to increased workload, fear of infection, and a shift toward remote care. Uncertainty regarding pregnancy-specific clinical guidelines and standard operating procedures (SOPs) contributed to reliance on general protocols and informal practices, while delayed hospitalization was linked to symptom denial, fear of admission, self-treatment, and system constraints. Pregnant and postpartum women commonly misinterpreted COVID-19 symptoms as pregnancy-related or mild illness, leading to self-medication and delayed help-seeking. Follow-up was largely unstructured and based on communication via phone or messages. The experience of care varied, ranging from timely clinical support to inconsistent monitoring and preference for home-based management.  Conclusion: The study offers detailed insights into a fragile and fragmented COVID-19 care pathway for pregnant women in primary and hospital care settings in Almaty. Several priorities for strengthening care organization for pregnant women with COVID-19 and for future public health emergencies include improving continuity of care, reducing delays in escalation, and enhancing the safety of maternal health services during infectious disease outbreaks.
Keywords: pregnancy; COVID-19; qualitative study; maternal health care; organization